PEMANFAATAN SENI KOLASE SEBAGAI PRODUK KREATIF UNTUK PENGEMBANGAN KARYA PROYEK STUDI MAHASISWA JURUSAN SENI RUPA FBS UNNES - Fiyanto, Arif (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2018)
Efforts to develop artworks from student study projects at the FBS UNNES Department of Fine Arts which choose collage art are very interesting when applied to tottebag, as a creative product. After going through observations and various considerations, collage artworks that have been worked on as student study projects will be more economically valuable, and become creative products. So that the work can collaborate into handmade products with archipelago images. Because the material used in making these products uses batik patchwork with designs that utilize Indonesian decorative motifs, especially in developing the tourism potential of Semarang. Thus the use of collage art as a creative product for the development of student study project works can be a research that discusses inspirational and innovative methods of development.Â Keywords: study projects, creative products, collage art